Vanuatu : Staff Report for the 2015 Article IV Consultation and Request for Disbursement Under the Rapid Credit Facility and Purchase Under the Rapid Financing Instrument. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that Vanuatu's Real GDP is expected to decline by 2 percent in 2015 because of the cyclone damage to Vanuatu's main export sectors-tourism and agriculture-which will be only partially offset by reconstruction activities and infrastructure investment. Risks to the outlook are biased to the downside since reconstruction may be constrained by availability of funding and by implementation capacity. Public sector recovery needs are estimated at about 20 percent of GDP. In 2016, a recovery in tourism and agriculture combined with further ramping-up of infrastructure projects is expected to propel growth to 5 percent.